Momentum in smart beta exchange-traded funds - Larsen, Elias Taneli Matti (My University, 2020)
Momentum is one of the most puzzling pricing anomalies discussed in the academic literature as past returns should not predict future returns under the efficient market theory. Asset pricing models have failed to explain momentum returns across different markets and asset classes while academics have argued about the reasons behind the success of momentum strategies. Momentum is stronger among industries and many papers have studied industry momentum in exchange-traded funds. More recent evidence suggests that industry and individual stock momentums originate from factor momentum. This thesis aims to extend factor momentum into the universe of exchange-traded funds by implementing relative-strength and time-series momentum strategies in 24 smart beta exchange-traded funds traded on the U.S. over the sample period of August 2000 to February 2020. Implementation of momentum strategies generates substantially large transaction costs due to the high trading volume required by the strategies. Smart beta exchange-traded funds offer investors easier access to factor momentum strategies with lower transaction costs. Thus, the purpose of this thesis is to examine whether individual investors can gain similar abnormal factor momentum returns documented in earlier studies by exploiting momentum strategies in smart beta exchange-traded funds. This thesis contributes to the earlier momentum studies in exchange-traded funds with a longer sample period that provides further evidence over the post-crisis period of the recent financial crisis. Three regressions of the Fama-French three, five, and six-factor models are used to test the profitability of the momentum strategies. Contrary to the results of factor momentum documented in earlier studies, the results from the regression models show that all abnormal returns are either negative or statistically insignificant. Furthermore, the results show that exchange-traded fund momentum strategies remain unprofitable with a longer post-crisis sample period. The thesis concludes that momentum strategies in smart beta exchange-traded funds are unprofitable and investors are not able to achieve abnormal returns by exploiting these strategies. The differing results with the earlier factor momentum studies might emerge from the simplistic factor approach used by the smart beta exchange-traded funds that could lead to unintended factor exposures. The exchange-traded fund market might also be more efficient than the stock markets. Another explanation for the failure of momentum in exchange-traded funds could be the small spreads between the past winners and losers. Future research could try to explain the reasons behind the reported momentum discrepancies between exchange-traded funds and individual stocks.
Keywords: exchange-traded funds; profitability; anomalies; strategies; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance; Finance